Desenvolvimento de procedimentos automáticos para determinação de etanol, glicerol e ácido tartárico em vinho empregando multicomutação em fluxo - Fernandes, Elizabeth Nunes (2004)
In the present work, flow systems for the determination of ethanol, glycerol and tartaric acid in wine without previous sample treatment are described. The flow system were based on multicommutation and controlled by microcomputer allowing that the analytic procedures were accomplished automatically without the intervention of the operator. For ethanol determination the proposed procedure employed detection by chemiluminescence using equipment developed in the Centro de Energia Nuclear na Agricultura. The detection device comprised a glass flow cell that was installed between two photodiodes forming a compact unit that was packed into a metallic box. The procedure for ethanol determination was based on the enzymatic reaction using alcohol oxidase producing acetaldehyde and hydrogen peroxide. The hydrogen peroxide reacted with luminol catalyzed by potassium hexacianoferrate (III) producing chemiluminescence. The luminescence intensity presented a direct relationship with ethanol concentration. The system allowed wine sample analysis without any prior treatment, presenting linear response between 2.5 and 25% (v/v) of ethanol characterized by the equation Signal (mV) = (20 ± 1) + (7.8 ± 0.3) % of ethanol (r = 0.997), a coefficient of variation of 1.8% for a typical wine sample presenting 11 % (v/v) of ethanol and a sampling frequency of 28 determinations for hour. For glycerol determination it was based on the reaction with glycerol dehydrogenase in presence the cofactor NAD+, resulting in oxidation of NAD+ to NADH that was monitored at 340 nm. After system optimization, a linear response between 2.0 and 10.0 g l-1 of glycerol characterized by the equation Abs = (0.1320 ± 0.003) + (149x10-4 ± 4x10-4) g l-1 of glycerol (r = 0.998), a coefficient of variation of 1.6% for a typical wine sample presenting 5.3 g L-1 of glycerol and a sampling frequency of 33 determinations for hour were obtained. For tartaric acid determination a single line module of analysis was designed, based on the reaction with vanadate and detection was carried out by spectrophotometry at 490 nm after reaction with sodium vanadate. The procedure presented a linear relationship between 0.50 and 10.0 g l-1 of tartaric acid characterized by the equation Abs = (0.206 ± 0.001) + 0.0404 ± 2.76x10-4 g l-1 of tartaric acid (r = 0.999), a coefficient of variation of 2.1% for a typical wine sample presenting 1.84 g L-1 of tartaric acid and a sampling frequency of 28 determinations for hour. Comparing the reagent consumption with earlier works it was observed that reduction about 65% was obtained. The three systems that comprise this work when applied to analysis wine samples presented results, which compared with results obtained using official methods no significant difference at 90 % confidence level were observed.